1997
DOI: 10.1055/s-0038-1657705
|View full text |Cite
|
Sign up to set email alerts
|

Human Longevity and R506Q Factor V Gene Mutation

Abstract: Senescence evolves as a direct consequence of the ebbing of natural selection via antagonistic pleiotropy or active selection for alleles with early life benefits combined with harmful effects in later life (l). Resistance to activated protein C is caused by the substitution of arginine with glutamine at position 506 in the factor V gene and is due to a single point mutation in one of the two cleavage sites of activated protein C in the factor V gene. It was found to be a major factor involved in thrombophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…However, as a matter of fact factor V Leiden carriership has no major effect on the overall life expectancy 69 and is compatible with extreme longevity, being present in centenarian individuals at the same rate (3.9 to 4.0%) than in noncentenarians (2.6 to 5.6%). 22,70…”
Section: Distribution Of Factor V Leiden Mutation In Different Populamentioning
confidence: 99%
“…However, as a matter of fact factor V Leiden carriership has no major effect on the overall life expectancy 69 and is compatible with extreme longevity, being present in centenarian individuals at the same rate (3.9 to 4.0%) than in noncentenarians (2.6 to 5.6%). 22,70…”
Section: Distribution Of Factor V Leiden Mutation In Different Populamentioning
confidence: 99%
“…We decided to exclude patients for whom the diagnosis of venous thromboembolism was ruled out and who had a personal history of venous thromboembolism; we believe those patients were not good controls because they already suffered from venous thromboembolism. Previous studies have suggested that factor V Leiden mutation was not associated either with a reduced life expectancy (24)(25)(26)(27) nor with the occurrence of cardiovascular events (18,28). Could our selection process explain that patients over 70 years with venous thromboembolism had a far lower prevalence of APC resistance?…”
Section: Discussionmentioning
confidence: 88%
“…Up to now, at least three single tests (for protein C, protein S, and APC resistance) were used simultaneously to look for defects in this inhibitor system. To simplify this approach, a number of screening tests which claim to recognize all known defects of the protein C pathway have been developed (3)(4)(5)(6)(7). In the present study, a new commercially available assay -Protein C Pathway Test (Gradipore Ltd., North Ryde, Australia) -was evaluated for clinical routine.…”
mentioning
confidence: 99%